The Nuance of Meaning and Kind of Synonymy Sensory Response Adjective in Indonesian - Nila Oktami; Ngusman Abdul Manaf; Novia Juita (International Conferences on Educational, Social Sciences and Technology)
Absolute synonymy never encountered in any language. The near synonyms still have different meanings, though only in nuances. If there is no difference in nuance between the pairs of synonyms then one of the words will disappear from the vocabulary. This study aims to explain the nuances of meaning and kind of pair synonym sensory response in Indonesian adjektive. This research is a qualitative descriptive method. The results showed that: (1) not all sensory responses Indonesian adjectives have a pairs synonym; (2) there are different nuance of meaning in every pair of synonymous sensory response adjektive; and (3) only two kind of synonymy in pairs synonymous sensory response adjectives was found, they are complete and absolute, and incomplete and not absolute. Synonyms word can concretize the use a personal language, so that trought language the communication is clear interesting. Paying attention to nuances of meaning that is synonymous Indonesian adjectives in speaking and writing can add color, sharpness, and precision of the wording.